On the Spread of the Novel Influenza A (H1N1) Virus in Mexico - Malaquias López-Cervantes; Aida Venado; Andrés Moreno; Reyna L. Pacheco-Domínguez; Guadalupe Ortega-Pierres (Journal of Infection in Developing Countries)
A novel influenza A H1N1 virus of swine origin is responsible for the influenza epidemic affecting Mexico, the United States of America (USA), and 39 other countries. While the origin of this emerging pathogen remains uncertain, an increase in the reported incidence of respiratory diseases was noted during March 2009 at the town of La Gloria, in the southeastern state of Veracruz, Mexico. So far, this is the first community in which a case of novel influenza A H1N1 virus has been identified. Further cases were rapidly detected in other areas of Mexico and elsewhere. Initially, the atypical respiratory disease outbreak caused great uncertainty posing a challenge to the Mexican health system. Control measures such as social distancing, timely medical care, and personal hygiene have so far proven effective in containing the outbreak, resulting in a decline of the number of new cases. To the best of our knowledge, it appears that the virus might not be as virulent or contagious as previously thought. Here we provide a description of the influenza epidemic spread in Mexico. As the virus disseminates worldwide, there is concern about the possibility of a new reassortment resulting in a more pathogenic strain that will pose a threat for every country. The influenza epidemic provided lessons that underscore the importance of epidemiologic surveillance and preparedness. Further investigation to address questions about this new virus and conditions for its spread is warranted.